Catalytic Esterification of Palm Fatty Acid Distillate to Produce Fatty Acid Methyl Ester - Kamis, W. Z. Wan; Azuwar, W. N.; Bashah, N. A. Ali; Isa, N.; Syed-Hassan, S. S. A. (New Trends in Physical Science Research Vol. 4, 2022)
Biodiesel, also known as fatty acid methyl ester (FAME), is a type of industrial and transportation fuel created by the esterification process. The esterification of palm fatty acid distillate (PFAD) to produce FAME was catalyzed in this study using a chromium-titanium mixed oxides catalyst produced by the sol-gel method. The esterification process was carried out in a batch reactor. The objectives were to study the effects of reaction temperature, methanol to PFAD molar ratio, reaction time and reusability of catalyst in the esterification of PFAD. The greatest performance of 89 percent FAME content was achieved with a reaction temperature of 160°C, a methanol to PFAD molar ratio of 3:1, and a reaction time of 3 hours. Between the first and third runs, the catalyst can be reused three times with a 20% performance reduction. The findings demonstrated that Cr-Ti mixed oxides might be used as a heterogeneous catalyst in the esterification of high acid value PFAD feedstock.